Structure-activity relationship study of Aib-containing amphipathic helical peptide-cyclic RGD conjugates as carriers for siRNA delivery. Issue 24 (15th December 2017) - Wada, Shun-ichi; Takesada, Anna; Nagamura, Yurie; Sogabe, Eri; Ohki, Rieko; Hayashi, Junsuke; Urata, Hidehito
Graphical abstract: Carriers for siRNA:PI : acetyl-KLULKLULKULKAULKLUG C(cRGDfC) -NH2 ;PII : acetyl- C(cRGDfC) KLULKLULKULKAULKLUG-NH2 ;PIII : acetyl- C(cRGDfC) KLULKLULKULKAULKLUG C(cRGDfC) -NH2 . Abstract: The conjugation of Aib-containing amphipathic helical peptide with cyclo(-Arg-Gly-Asp-d -Phe-Cys-) (cRGDfC) at the C-terminus of the helix peptide (PI ) has been reported to be useful for constructing a carrier for targeted siRNA delivery into cells. In order to explore structure–activity relationships for the development of potential carriers for siRNA delivery, we synthesized conjugates of Aib-containing amphipathic helical peptide with cRGDfC at the N-terminus (PII ) and both the N- and C-termini (PIII ) of the helical peptide. Furthermore, to examine the influence ofPI helical chain length on siRNA delivery, truncated peptides containing 16 (PIV ), 12 (PV ), and 8 (PVI ) amino acid residues at the N-terminus of the helical chain were synthesized.PII andPIII, as well asPI, could deliver anti-luciferase siRNA into cells to induce the knockdown of luciferase stably expressed in cells. In contrast, all of the truncated peptides were unlikely to transport siRNA into cells.